P179 Forced vital capacity, systemic inflammation and cardiometabolic markers in adulthood: a cross-sectional analysis. (14th November 2013) - Saad, NJ; Kaakinen, M; Da Silva Couto Alves, A; Minelli, C; Jarvelin, MR; Burney, PGJ
Abstract : Introduction: Forced vital capacity (FVC) is a powerful predictor of mortality, more than airflow obstruction (Burney et al . Thorax 2011;66:49–54). FVC is associated with systemic inflammation as well as with cardiovascular disease and diabetes. Given that systemic inflammation is also associated with cardiovascular disease and diabetes, systemic inflammation could explain the observed association between FVC and cardiometabolic markers. Here, we examined the association between FVC, cardiometabolic markers and systemic inflammation in 3, 731 individuals belonging to the Northern Finland Birth Cohort 1966. Methods: Using linear regression, we examined the association between i) cardiometabolic markers (systolic blood pressure, diastolic blood pressure, LDL cholesterol, triglycerides, fasting glucose, insulin and HOMA-IR) and inflammatory markers (C-reactive protein (CRP) and white blood cell count (WBC)), ii) FVC and inflammatory markers, and iii) FVC and cardiometabolic markers. We then tested whether the association between FVC and cardiometabolic markers could be explained by systemic inflammation, by adjusting the linear regression models of FVC on each cardiometabolic marker for the two inflammatory markers. Results: Increasing levels of inflammatory markers were associated with a decrease in FVC, -12mL per mg/L of CRP (95% confidence interval (CI): -17 to -7 mL) and -17 mL per 10 9 cells/L of WBC (95% CI: -28 to -7 mL), and with increasing levels of the cardiometabolic markers. FVC also decreased with increasing levels of cardiometabolic markers (Table, column 1) and adjusting these associations for the inflammatory markers did not substantially alter them (Table, column 2). Conclusion: The association between FVC and cardiometabolic markers is not explained by variation in inflammatory markers, as measured by CRP and WBC. However, due to the cross-sectional nature of the analysis, no inference can be made with regard to the directionality of the associations.